(untitled) (Research, Society and Development, 2022)
Objective: to characterize, through the national literature, the care tools used by nurses to identify depressive symptoms in the elderly population they care for. Method: Integrative Literature Review that searched for national articles written between the years 2015-2021 that dealt with the tools used by nurses to assist in the screening of senile depression. The manuscripts were filtered in the following platforms: Scientific Eletronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Virtual Health Library (BVS), using cross-references with the following descriptors available on the Health Science Descriptors (DeCS) website: Depression, Elderly, Nursing and Geriatric Nursing. Results: A total of 15 articles were selected for the search, mostly from the year 2020. The Geriatric Depression Scale was the main instrument of choice for nurses, together with the anamnesis process. From the results, three categories of discussion were listed: "main scales for screening depression in the elderly", "healthy aging and depression: loneliness and resilience in old age", and "nurses’ actions when screening for depression". Final Considerations: The nurses used multidimensionais approaches, which allowed for the assessment of other important parameters for the quality of life of the elderly in addition to the depressive state. However, attention is drawn to the need to create new instruments directed at the object of Nursing and a greater appropriation of the NP, allowing for the prioritization of care centered on the person and his/her needs, optimizing care and assistance.